Control and monitoring system of Railway level crossings for traffic safety based on IoT - Lovella, Nadillah; Yuhendri, Muldi (Journal of Industrial Automation and Electrical Engineering, 2025)
Accidents at railroad crossings still frequently occur due to the negligence of road users and the lack of an optimal security system. This study aims to design a prototype of an Internet of Things (IoT)-based level crossing monitoring and control system to improve traffic safety. This system uses an ESP32 microcontroller as the control center, an HC-SR04 ultrasonic sensor to detect the arrival of the train, a servo motor as a driver for the automatic barrier gate, and Blynk IoT as a remote monitoring and control platform. The research method used is the waterfall model, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The results of the study show that the developed system can work automatically in detecting train arrivals, displaying crossing status on a 16x2 LCD, and providing warnings via LED indicators and buzzers. In addition, users can control the gate manually through a Blynk-based application. Based on the tests conducted, the system has a good level of accuracy in detecting the presence of trains and responding to commands from the application with a response time of less than 1 second. Thus, this prototype is expected to be an innovative solution to improve safety at railroad crossings and reduce the risk of accidents due to human error